Minat Baca E-book di Perpustakaan SMAN Jatinangor - Puti Nabila, Shazia; Khairul Anwar, Rully; Rukmana, Evi Nursanti (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Students’ interest in reading e-books at SMAN Jatinangor remains relatively low, despite the strong potential of e-books as digital literacy resources that support learning and academic achievement. This condition is influenced by several factors, including the dominance of online entertainment content, the use of digital devices mainly for social media, and long-established learning habits centered on printed books. These challenges require school libraries to adapt their services by strengthening digital collections, promoting electronic-based literacy, and providing inclusive access while maintaining reading comfort and content quality. This study aims to analyze students’ interest in reading e-books at the SMAN Jatinangor Library using a descriptive qualitative approach. Data were collected through observation of e-book usage patterns and interviews to examine students’ experiences, preferences, and factors influencing their reading decisions. The findings reveal that students’ interest in e-books is influenced by individual factors such as literacy motivation, screen-reading comfort, academic needs, and learning habits, as well as social factors including peer support, teacher encouragement, and access to digital devices. The study concludes that interest in e-books has begun to increase due to their accessibility and efficiency, although printed books remain an important complementary resource, particularly for intensive reading activities that require sustained concentration.